The Murals of St. Gregory Church of Khachut in the Context of Byzantine and Transcaucasian Art of the Late 12th – First Third of the 13th Centuries - Makarova, Anna L. (Actual Problems of Theory and History of Art, 2024)
The article analyzes the style of paintings of the Church of St. Gregory of Khachut in Ani based on surviving fragments from the State Hermitage Museum (St. Petersburg). The church was discovered during the first archaeological campaign of N. Y. Marr in 1892. As a result of the excavations seventy-two stones with paintings were discovered, three of them were deposited in the Hermitage, the fate of the rest is unknown to date. The study determines the originality of the artistic methods of the painting of the Church of St. Gregory, which, on the one hand, distinguish it against the background of Armenian and Georgian ensembles of the turn of the 12th–13th centuries, and, on the other hand, show the stylistic commonality with the Byzantine art of that time. The paintings of St. Gregory’s church are conservative, they are clearly oriented to the monuments of earlier times, belonging to the “asceticizing trend”, which became relevant again in the early 13th century. As the closest analogies to the fragments from St Gregory’s church, we suggest such monuments as icons from the State Tretyakov Gallery: the Mandylion (the last third of the 12th century) and the Assumption of the Mother of God (the beginning of the 13th century), miniatures of a Georgian manuscript (A-26, the beginning of the 13th century), National Center of Manuscripts, Tbilisi) and others. The paintings of St. Gregory’s Church overcome the expression and emotionality of the Comnenian style and are characterized by contemplation and calmness, which allows us to see the monument in the line of the new line of development of the style of the beginning of the century. A benchmark example of such art are the frescoes of the Church of Our Lady in Studenica (1208–1209). The study has been realized by the grant of the Russian Science Foundation, project no. 22-18-00354, https://rscf.ru/project/22-18-00354/, in the Moscow State University of Civil Engineering (MGSU), National Research University.